Pimpla Fabricius (Hymenoptera: Ichneumonidae: Pimplinae) from Colombia - Pádua, Diego G.; Araujo, Rodrigo O.; Mazariegos, Luis A. (Zootaxa, 2019)
Pimpla Fabricius is one of the largest genera within the subfamily Pimplinae, whose species are idiobiont endoparasitoids of Lepidoptera pupae and prepupae. A total of 13 species are known from Colombia, but they are difficult to identify because of their morphological complexity. Herein we record for the first time in Colombia the following species: P. albomarginata Cameron, P. caerulea Brullé and P. sumichrasti Cresson. Furthermore, we present the first identification key to female and male of the Colombian species, along with diagnoses, biological notes and images in vivo.